2015
DOI: 10.1128/jvi.01765-15
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Serial Infections with H13 and H16 Low-Pathogenic Avian Influenza Viruses in Black-Headed Gulls

Abstract: Infections of domestic and wild birds with low-pathogenic avian influenza viruses (LPAIVs) have been associated with protective immunity to subsequent infection. However, the degree and duration of immunity in wild birds from previous LPAIV infection, by the same or a different subtype, are poorly understood. Therefore, we inoculated H13N2 (A/black-headed gull/Netherlands/7/ 2009) and H16N3 (A/black-headed gull/Netherlands/26/2009) LPAIVs into black-headed gulls (Chroicocephalus ridibundus), their natural host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
7
32
1
1
Order By: Relevance
“…A possible explanation of this inconsistency is that these truncated antibodies neutralize IAV but lack HI activity (20). Our results are in agreement with other studies in both ducks and gulls that reported partial to complete protection against re-infection depending on the viruses, time between infections, host species and age and detection method (9,21,22). The long-term persistence of antibodies after natural infection, artificial challenge or vaccination has been reported in captive birds up to 6 to 9 months post-exposure (23-25) though it is not know which parameters (i.e.…”
Section: Homologous Challengesupporting
confidence: 88%
See 1 more Smart Citation
“…A possible explanation of this inconsistency is that these truncated antibodies neutralize IAV but lack HI activity (20). Our results are in agreement with other studies in both ducks and gulls that reported partial to complete protection against re-infection depending on the viruses, time between infections, host species and age and detection method (9,21,22). The long-term persistence of antibodies after natural infection, artificial challenge or vaccination has been reported in captive birds up to 6 to 9 months post-exposure (23-25) though it is not know which parameters (i.e.…”
Section: Homologous Challengesupporting
confidence: 88%
“…With equal strength of HA immunity to all subtypes the present antigenic diversity found in wild birds would be unlikely. Surprisingly, the results from H13 and H16 experimental infections in black-headed gulls showed limited cross-immunity between subtypes and suggest independent cycles for these viruses (21).…”
Section: Antibody Dynamicsmentioning
confidence: 85%
“…It has been particularly challenging to quantify changes in acquired immunity with age, because the exact ages of wild-caught birds are usually unknown or because lifespans of many domestic bird species that harbour AIV are too short for meaningful patterns to be discerned. An experimental study of wild-caught gulls reared in captivity showed that exposure to AIV results in increased protection against that strain for at least 1 year [19], suggesting that continual exposure to AIVs could result in better protection with increased age. However, while experimental studies provide important insights under controlled conditions, they may not adequately describe long-term acquisition of immunity in wild populations that are exposed to a diverse range of AIV subtypes over prolonged periods and to other sources of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, seasonal peaks in viral prevalence have been observed following hatching, and attributed to the immunological naivety of the unfledged birds [29]. Immunologically naive birds that are challenged by an AIV have similar shedding patterns and probability of seroconversion, regardless of bird age [19]. It is therefore likely that the age-related patterns of seroprevalence and viral prevalence observed in the wild result from birds gaining immunity to AIV with continual exposure throughout the lifespan, rather than changes in immune function specifically resulting from ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 16 described avian influenza virus hemagglutinin subtypes, H13 and H16 are associated to seabirds . Although low pathogenic virus subtypes do not induce clinical signs of disease (Brown et al, 2012;Verhagen et al, 2015), infection with highly pathogenic avian influenza viruses (H5 and H7 subtypes) can induce severe clinical signs. These subtypes can cause cloudy eyes, ruffled feathers, weakness, a lack of coordination, torticollis, and mortality (Brown et al, 2006).…”
Section: Avian Influenzamentioning
confidence: 99%